Clinical outcomes of definitive whole pelvic radiotherapy for clinical lymph node metastatic prostate cancer. (4th August 2020) - Tsuchida, Keisuke; Inaba, Koji; Kashihara, Tairo; Murakami, Naoya; Okuma, Kae; Takahashi, Kana; Igaki, Hiroshi; Nakayama, Yuko; Maejima, Aiko; Shinoda, Yasuo; Matsui, Yoshiyuki; Komiyama, Motokiyo; et al.
Abstract: Background: In this study, we aim to present the clinical outcomes of radiotherapy (RT) in clinical pelvic lymph node‐positive prostate cancer (cN1) patients. We also analyze the prognostic factors with focus on RT dose escalation to metastatic lymph nodes (LN). Methods: We retrospectively analyzed the data from cN1 patients who were treated with definitive RT and androgen deprivation therapy (ADT) between June 2004 and February 2016. All patients received localized irradiation to the prostate region and whole pelvis irradiation. Some patients received intensity‐modulated radiation therapy with RT dose escalation to metastatic LN. Univariate analyses using log‐rank test were performed to find prognostic factors between patient subgroups. Results: Fifty‐one consecutive patients were identified. The median follow‐up period for all patients was 88 (range 20‐157) months. Primary Gleason pattern and LN RT dose were statistically significant prognostic factors for relapse‐free survival (RFS) and distant metastasis‐free survival (DMFS). Especially, RT dose escalation (60 Gy or more) to metastatic LN significantly improved RFS and DMFS compared with standard dose RT (4‐year RFS 90.6% vs 82.1%, 7‐year RFS 90.6% vs 58.0%, P  = .015; 4‐year DMFS 90.6% vs 82.1%, 7‐year DMFS 90.6% vs 62.8%, P  = .023). The following factors were all statistically significant for biochemical relapse‐free survival (BRFS): T stage, LN RT dose, local RT dose, and ADT duration period. Any significantly different toxicity was not seen for each LN or local RT dose except for the incident rate of grade 2 or more acute urinary retention, which was significantly higher in the higher LN RT dose (60 Gy or more) group by the Chi‐square test. Conclusions: RT dose escalation to metastatic LN in cN1 patients improves BRFS, RFS, and DMFS at 4 and 7 years, without increasing severe adverse events. Abstract : In this retrospective study, we aim to present the clinical outcomes of radiotherapy (RT) in clinical pelvic lymph node‐positive prostate cancer (cN1) patients. We also analyze the prognostic factors with focus on RT dose escalation to metastatic lymph node (LN). RT dose escalation to metastatic LN in cN1 patients improves relapse‐free survival (RFS) and distant metastasis‐free survival (DMFS) at 4 and 7 years, without increasing severe adverse events.